(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
The English language has undergone remarkable changes throughout history and has become the dominant means of international communication in the modern world. This paper discusses the historical stages of English development, the main factors influencing its growth, and its current role as a global language in education, science, and technology.